FORMATION OF ECOLOGICAL KNOWLEDGE AND CULTURE IN TOURISM - Mirzakarimov M. (American Journals, 2024)
The passage discusses the formation of ecological knowledge and culture in the context of tourism. It highlights the importance of developing ecotourism and informing the international community about the region's ecotouristic potential. The passage emphasizes the need to protect nature, use natural resources wisely, and preserve the beauty and purity of the environment. It also addresses the global ecological crisis and the role of ecotourism in promoting the preservation of nature and educating people to be ecologically literate and culturally aware. The passage emphasizes the connection between ecology and economy, underlining the need to manage our natural "household" in harmony with nature. It underscores the significance of ecological stability, comfortable natural environments, and sustainable resource use. Overall, the passage emphasizes the importance of ecological awareness, consciousness, and a spiritual connection with nature in fostering ecological knowledge and culture within the tourism industry.
Keywords: Formation, ecological knowledge, culture, tourism, ecotourism, international community, region, potential, nature, natural resources, environment, global ecological crisis, preservation, education, ecological literacy, cultural awareness, ecology.